Germany and the next war - Bernhardi, Friedrich von, 1849-1930 (Longmans, Green, and Co., 1914)
Brilliant and bellicose book on the divine nature of warfare and the proper place of Germany in the modern world by a leading Prussian militarist. Bernhardi viewed war as "a biological necessity" based upon "the natural law ... the law of the struggle for existence." Originally published in 1911, the book influenced German military thinking in both World War I and World War II.